(untitled) (Research, Society and Development, 2023)
Scientific literature supports a positive relationship between physical activity and physical and mental health outcomes. During the social isolation resulting from the new coronavirus (COVID-19), significant reductions in physical activity levels were reported, an event that may have had negative effects on the health of the population. The objective of this protocol is to describe the proposal for a scoping review, whose objective is to map and synthesize the main discoveries presented in the scientific literature about the relationship between physical activity and health during the period of social isolation resulting from COVID-19. The proposed scoping review will be reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-analyses extension for Scoping Reviews (PRISMA-ScR). Web of Science and PubMed® will be consulted to identify observational or experimental studies that have analyzed the relationship or effect of physical activity on health outcomes during social isolation due to COVID-19. Studies identified in the databases will be entered into Rayyan®. Subsequently, two reviewers will be responsible for screening the studies. After screening, two reviewers will be responsible for extracting the data, which will be exposed in the review through a qualitative synthesis, supported by descriptive statistics.